Karya Ilmiah Terapan Sistem Pendeteksi Gempa Menggunakan Arduino di Pelabuhan SMI Shipyard Banjarnegara - Priyo Lanang Eka Wicaksono (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Indonesia is a country located between active earth plates, namely the Eurasian Plate, the Indo- Australian Plate, and the Pacific Plate. These plates are very active plates that move and pose a high risk of earthquake disasters. Therefore, the author wrote an Applied Scientific Work with the title Earthquake Disaster Detection System Using Arduino at the SMI Shipyard port. Earthquake Detection System is made in order to detect earthquake disasters and minimize casualties due to the earthquake disaster. The use of these tools in the world of transportation to detect earthquakes used in coastal areas and port ports located in earthquake-prone areas. The method used is system design to determine the occurrence of an earthquake or vibration detected by the ADXL 355 sensor to reach the output, namely the buzzer and LCD. From that the author makes a tool that can provide warnings to the community or workers in the area to avoid casualties. Earthquake Detection System Using Arduino gives output commands to the buzzer and 220 V lamp. If the vibration is from 2.0 SR, the buzzer and light output will not be active. This system has an accuracy rate of 77.6% and has the largest error rate of 22.4%.